Ethnobotanical study on medicinal plant knowledge among three ethnic groups in peri-urban areas of south-central Ethiopia - Sintayehu Tamene; Mesele Negash; Fortunatus Bulabo Makonda; Linley Chiwona-Karltun; Kefyalew Sahle Kibret (BMC, 2023)
Abstract Background Documenting traditional knowledge on plant use among ethnic groups has enabled researchers to obtain a better understanding of how indigenous flora is seen and used in daily life. Their therapeutic applications will also encourage future conservation and phytochemical research, potentially leading to the development of novel drugs. However, past ethnobotanical studies conducted in Ethiopia mainly focused on rural areas, and limited coverage to document the ethnobotanical knowledge at the rural‒urban interface. Therefore, this study was conducted to document and analyze traditional ethnobotanical knowledge on medicinal plants among three selected ethnic groups in peri-urban areas of south-central Ethiopia. In addition, we attempted to investigate the range of cultural similarity and disparity between the studied ethnic groups in relation to traditional medicinal plants and diseases treated. Methods Data were collected using semistructured questionnaires and in-depth interviews of 189 key informants, floristic species inventories, and field observations. Several cultural importance indices and Rahman's similarity indices were applied to analyze the relevance of medicinal plants and cultural similarity among the ethnic groups. Results A total of 189 therapeutic plants representing 159 genera and 69 families were identified and documented across the three studied ethnic groups. Of these, the Sidama, Gedeo, and Oromo ethnic groups reported 28, 34, and 38%, respectively. Most medicinal plants were represented by herbs (36%), followed by shrubs (31%), trees (27%), and herbaceous climbers (7%). Rahman's similarity index (RSI) revealed considerable ethnobotanical knowledge variation among ethnic groups. Oromo and Sidama showed the highest disparity (63.8%), followed by Gedeo and Oromo (63.2%). Of the total collected therapeutic plants, 78 most important medicinal plants were selected for the cultural importance analysis, which revealed that Croton macrostachyus Hochst. ex Delile scored the highest point in the Gedeo and Oromo ethnic groups and Zingiber officinale Roscoe in the Sidama ethnic group. Whereas Cinnamomum verum J.Presl, Psidium guajava L., and Melia azedarach L. are the least. Conclusion The present study revealed the presence of cultural differences in medicinal plant knowledge practices and therapeutic plant use among the studied ethnic groups in rural-urban interface areas of south-central Ethiopia. The diverse healing potential of plants would support future pharmacological investigations, emphasizing the need for adequate documentation of indigenous knowledge and versatile flora to prevent their further loss.